Association Between Birth Weight and Wasting in Children: A Case-Control Study - Citra Nur Indah Septiani; Ratnawati Ratnawati; Ulfah Dian Indrayani (International Journal of Human and Health Sciences (IJHHS), 2026)
Wasting is an acute malnutrition condition in children under five defined by WHZ